TEMPERATURE AND HEAT FLOW DENSITY IN A THICK CRATONIC LITHOSPHERE: THE SVEKA TRANSECT, CENTRAL FENNOSCANDIAN SHIELD - Kukkonen I.T. (My University, 1998)
Lithospheric temperatures and heat flow densities (HFD) were simulated in the 650 km long SVEKA transect in the central Fennoscandian Shield. The area is characterized by anomalously thick crust (up to 55 km) and lithosphere (170–200 km). The investigated transect extends from the Archaean granite-greenstone terrain in the NE to an Early-Middle Proterozoic domain in the SW composed of metasediments, metavolcanics, granitoids and other igneous rocks.The significance of heat transfer by circulating fluids in the crust was investigated with numerical simulations. Significant deviations from conductive conditions are possible given that hydraulic permeability and hydraulic gradient are sufficiently big. Measured values of in situ permeability and the low topographic variation in the transect area, however, do not support the existence of flow systems which would be thermally relevant in the crustal scale. Therefore, heat transfer is considered mainly conductive in the crust. In the mantle, radiative heat transfer is assumed to be active in addition to conduction.Thermal conductive simulations which were based on the available information on geological, seismic, potential field and HFD investigations of the area suggest the following results: 1.1. the seismic lithosphere/asthenosphere boundary at the depth of 170–200 km is at the solidus of volatile-bearing peridotite (about 1100 ± 100 °C);2.2. Surface HFD is to a large extent controlled by heat production in the upper crust, which is responsible for about 30–45% of the surface HFD signal;3.3. lithosphere thickness variations are not reflected in HFD variations on the studied transect, mainly because the L/A depth varies only about 20 km along the transect;4.4. mantle HFD is low (about 12 ± 5mWm−2) along the transect and5.5. temperature at 50 km level (approximately at Moho) increases from the Archaean domain (about 400 °C) to the Proterozoic (500 °C) end of the transect.Accuracy of temperature estimation is affected by the applied conductivity and heat production values, and the extreme bounds of the estimated Moho temperatures may be either about 100 K lower or 200 K higher than the values above. These limits correspond to conductivit
Keywords: Archaean; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой; Докембрий::Архей; Precambrian::Archean